دور المدرسة في تربية المواطنة - بالطاهر, النوي (Sciences de l'Homme et de la Société, 2012)
إن تربية المواطنة جزء لا يتجزأ من مهام المدرسة، والتربية على المواطنة ليست معرفة فقط ولكن ممارسة تلقن للتلاميذ للتفاعل والعيش معا من خلال نشاطات ملموسة تسمح لهم ببناء فضاءات المواطنة.        في هذا الإطار، تعمل المدرسة على تنمية الحس المدني لدى التلاميذ وتنشئتهم على قيم المواطنة، وتجذير الشعور بالانتماء للوطن في نفوس التلاميذ  وتنشئتهم على حب الوطن، تنمية ثقافة ديمقراطية لدى التلاميذ بإكسابهم مبادئ الحوار والتسامح والتعاون ونبذ العنف والتعصب، تكويــــــن مواطنين قادرين على تحمل المسؤولية في حياتهم الشخصية والاجتماعية. تنمية ثقافة ديمقراطية لدى التلاميذ بإكسابهم مبادئ الحوار والتسامح والتعاون ونبذ العنف والتعصب، تكويــــــن مواطنين قادرين على تحمل المسؤولية في حياتهم الشخصية والاجتماعية.     The citizenship education is an integral part of the tasks of the school, and civic education is not knowledge only, but exercise taught the students to interact and live together through concrete activities that allows them to build spaces of citizenship          In this context, the school operates on the development of a sense of the civil to the pupils and their development on the values of citizenship, and entrenching a sense of  belonging to the homeland in the hearts of students and their development on the love of the homeland, the development of a democratic culture among students gains the principles of dialogue, tolerance, cooperation and non-violence and intolerance, configure the citizens are able to take responsibility in their personal lives and social.